MEASUREMENT OF TECHNOLOGY AND MANUFACTURING READINESS LEVEL FOR PLANNING, CONTROLLING AND MITIGATION OF BUSINESS RISK IN AEROSPACE INDUSTRIES (CASE STUDY: KF-X/IF-X FIGHTER JOINT DEVELOPMENT PROGRAM) - Amperiawan, Gita
Measuring of technological and manufacturing readiness level are two approaches that NASA initially used to evaluate risks to space acquisition equipment. In its development, this method of measuring technology and manufacturing readiness extends not only to space technology but also to the process of acquiring or developing a military technology. One of the military technologies which use technology and manufacturing readiness measurement methods is fighter aircraft technology.